Modern interpretation of animistic metaphors: An example from Indonesia - Kahana, Reʾuven (Sojourn, 1993)
After providing a brief description of the place of animism in Indonesia society, this contribution presents some examples of manipulation of symbols through different channels. It points out that the common denominator shared by all these channels (the Kebatinan movement in Java, the Wayang shadow play, animistic metaphors in the Pancasila - state ideology of Indonesia - etc) of expression is their ability to transform symbols into living powers by conferring on them semi-spiritual meaning. (DÜI-Sen)